Symmetry control of nanorod superlattice driven by a governing force - Yujia Liang (Nature Portfolio, 2017)
Shape complementarity is the primary way to control the symmetry of nanoparticle assemblies. Here, the authors introduce a governing force that dominates symmetry control of nanorod superlattices, using it to obtain an unexpected and highly thermostable tetragonal lattice.